1986
DOI: 10.1021/bi00360a014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cholesterol and adrenodoxin binding on the heme moiety of cytochrome P-450scc: a resonance Raman study

Abstract: The effects of cholesterol and adrenodoxin binding on resonance Raman spectra of cytochrome P-450scc in both oxidized and CO-reduced states were examined. Upon cholesterol binding, oxidized cytochrome P-450scc showed a significant shift of spin equilibrium from low-spin to high-spin state. Addition of adrenodoxin caused a complete conversion of cholesterol-bound oxidized cytochrome P-450scc to a pure high-spin state that was considered to be in the hexacoordinated state judged by the v10 mode at 1620 cm-1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
68
2

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 37 publications
13
68
2
Order By: Relevance
“…In principle it is possible that the orientation to the heme in all substates is exactly the follow the trend observed for the average values-namely, larger CO-heme normal angles correspond to smaller CO stretch frequencies (23,24). Within the Al band, however, the behavior is opposite.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…In principle it is possible that the orientation to the heme in all substates is exactly the follow the trend observed for the average values-namely, larger CO-heme normal angles correspond to smaller CO stretch frequencies (23,24). Within the Al band, however, the behavior is opposite.…”
Section: Resultsmentioning
confidence: 70%
“…Fig. 4 shows a correlation between the center frequencies of the A bands and the average orientation of the bound CO in MbCO: Higher CO stretch frequencies correspond to CO orientations closer to the heme normal (21)(22)(23). The Ao substate, where the CO stretch frequency is closest to that of CO bound to protoheme, is closest to being perpendicular to the heme plane, establishing internal consistency.…”
Section: Resultsmentioning
confidence: 80%
“…On the other hand, we and others have shown that the nature of the guanidine substrate can significantly modify the oxidation chemistry, along with the resulting reaction intermediates and products (41,42,71,72). These considerations led us to address, in this work, the actual role of the guanidinium proton in the mechanism of NOS by analyzing the interactions between the heme active site and the guanidinium moiety of L (41, 55-57, 59, 69, 70) and cytochromes P450 (44,68,(73)(74)(75)(76). In addition to bond angles, the Fe-CO vibrational modes are very sensitive to the electrostatic and polar properties of the heme distal pocket because of changes in the back donation from the iron d* orbital to the empty * CO orbital (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…In this context we note that, based upon different spectroscopic techniques, it was suggested that in mammalian P-420 the thiolate is replaced by a hgand which exhibits much weaker electron-donating capabilities [15,. This may either be a histidine or the protonated thiolate residue.…”
Section: Inactivation Of Lm2 and Lm4mentioning
confidence: 91%